Mechanisms of Atlantic Meridional Overturning Circulation(AMOC) Variability in a Coupled Ocean-Atmosphere GCM - Huang, Boyin; Zhu Jiang; Yang Haijun (Advances in Atmospheric Sciences, 2014)
The mechanisms involved in the variability of Atlantic Meridional Overturning Circulation (AMOC) are studied using a 2000-yr control simulation of the coupled Fast Ocean-Atmosphere Model (FOAM). This study identifies a coupled mode between SST and surface heat flux in the North Atlantic at the decadal timescale, as well as a forcing mode of surface heat flux at the interannual timescale. The coupled mode is regulated by AMOC through meridional heat transport. The increase in surface heating in the North Atlantic weakens the AMOC approximately 10 yr later, and the weakened AMOC in turn decreases SST and sea surface salinity. The decreased SST results in an increase in surface heating in the North Atlantic, thus forming a positive feedback loop. Meanwhile, the weakened AMOC weakens northward heat transport and therefore lowers subsurface temperature approximately 19 yr later, which prevents the AMOC from weakening. In the forcing mode, the surface heat flux leads AMOC by approximately 4 yr. http://gateway.webofknowledge.com/gateway/Gateway.cgi?GWVersion=2&SrcApp=PARTNER_APP&SrcAuth=LinksAMR&KeyUT=WOS:000334180700001&DestLinkType=FullRecord&DestApp=ALL_WOS&UsrCustomerID=8e1609b174ce4e31116a60747a720701 Meteorology & Atmospheric Sciences SCI(E) 中国科技核心期刊(ISTIC) 中国科学引文数据库(CSCD) 2 ARTICLE boyin.huang@noaa.gov 2 241-251 31